Religious Commitment and Well-Being in College Students: Examining Conditional Indirect Effects of Meaning in Life - Dar, Kaiser Ahmad (Journal of religion and health, 2019)
There is systematic and quantitative evidence that religious commitment is associated with indicators of well-being, such as positive emotions and moods, absence of negative emotions, and satisfaction with life; however, researchers remain far from a consensus regarding which mechanisms may account for these observed relationships. Although religious commitment influences well-being through many different mechanisms, meaning in life is probably the predominant one. Thus, we examined the bidimensional conceptualization of meaning in life as a potential mechanism between religious commitment and well-being. The study was cross-sectional in nature. Survey data were collected from 92 college students, aged 17-21. A battery of self-report measures was used for tapping religious commitment, well-being, and meaning in life. Even though presence of meaning, search for meaning, religious commitment, and well-being correlated moderately with each other, presence of meaning carried a substantial proportion of variance in predicting well-being for girls/women. This study suggests that religious commitment influences a person's sense of meaning in life, which, in turn, influences her/his well-being. And, we hope that these results encourage professionals to explore with their clients the fundamental questions of meaning and purpose in life.